Interaction between CSL students’ motivation and anxiety under different L2 writing tasks: evidence from Vietnamese university students - Wang, Cong; Zhu, Sida; Zhang, Haijing (Frontiers in Psychology, 2023)
Improving task motivation can reduce anxiety and enhance the efficiency of second language (L2) learning. However, previous research has not determined whether the relationship between task motivation and anxiety is unidirectional facilitation or bidirectional interaction. The reasons for these "relationships" and their impact on L2 learning have not been analysed in depth yet. This study investigated the interaction between task motivation and anxiety via qualitative and quantitative research methods with the participation of 229 Vietnamese university students, who were divided into three L2 writing task groups, including the free choice group (FC), the limited choice group (LC), and the no choice group (NC). The quantitative results show that the higher individuals' autonomy levels were, the higher their task motivation levels would be. Besides, the high level of task anxiety reduced task motivation among Vietnamese university students and exited other anxiety factors. The qualitative analysis of semi-structured interviews conducted with 32 Vietnamese university students showed that a small number of negative factors might trigger low levels of task anxiety. Nevertheless, the results for participants with different levels of Chinese language proficiency were highly variable. Participants with better cognitive and Chinese language levels regarded task anxiety as an opportunity to practice their Chinese language skills. They were motivated to complete the task, while participants with lower Chinese language levels exhibited low confidence and experienced more challenges when completing the task.